Optimisation of silicone-based dielectric elastomer transducers by means of block copolymers – synthesis and compounding - A Razak, Aliff Hisyam (2017)
Emerging artificial muscle technology has developed from metal-based robotics to softtype robotics made from soft matter. Research into artificial muscle technology based on soft matter has been conducted mainly in order to mimic soft and robust human muscle. In this regard, dielectric elastomers have been studied. Their actuation occurs when Maxwell stress exceeds elastic stress in the presence of an electrical field, resulting in contraction in thickness and planar expansion in the area. As well as an actuator, dielectric elastomers can be used as generators and sensors. As a dielectric elastomer, silicones have been used extensively in many applications, due to favourable properties such as thermal stability, non-conductivity, high gas permeability and low toxicity. However, silicones have a low dielectric constant and thereby low energy density. In order to enhance actuation performance, it is the aim of this research to develop silicone elastomers with a high dielectric constant and high electrical breakdown strength, as well as a low Young’s modulus. In this Ph.D. thesis, two methods were developed to enhance silicone properties such as the dielectric constant and electrical breakdown strength. The first method was devised to enhance the dielectric constant of silicone elastomers through the use of a polydimethylsiloxane-polyethyleneglycol (PDMS-PEG) copolymer, in order to obtain an elastomer with high electrical energy. PDMS-PEG copolymers were synthesised and blended in commercial silicone and subsequently cross-linked. The relative permittivity of cross-linked silicone with 5 wt% of PDMS-PEG copolymers increased by nearly 50%, without compromising dielectric loss and mechanical properties, compared to the commercial silicone elastomer. The second investigated method involved enhancing the electrical breakdown strength of silicone by using an aromatic voltage stabiliser. Here, polyphenylmethylsiloxane (PPMS), which contained aromatic voltage stabilisers, was bonded covalently to PDMS through a hydrosilylation reaction obtaining PDMS-PPMS copolymers. The synthesised copolymers were subsequently cross-linked with a vinyl cross-linker. The obtained cross-linked PDMS-PPMS copolymers were inherently soft and robust with increased electrical breakdown strength (21%) compared to the reference elastomer without an aromatic voltage stabiliser. The conducting polymer was developed through the use of a multi-walled carbon nanotube (MWCNT) in a PDMS-PEG matrix as a compliant electrode of dielectric elastomers. The conductive PDMS-PEG copolymer was incorporated with surface-treated MWCNT, in order to obtain highly conductive elastomer. The prepared sample with 4 parts per hundred rubber (phr) MWCNT was soft and the resulting conductivity of the cross-linked PDMS-PEG copolymer with the addition of MWCNT was high, at 10-2 S cm-1, nearly equivalent to a commonly used commercial conducting polymer. In this thesis, the elastomer and electrode system is referred to as a ‘dielectrielastomer